A branch‐and‐cut‐and‐price algorithm for the mixed capacitated general routing problem. Issue 3 (22nd August 2016) - Bach, Lukas; Lysgaard, Jens; Wøhlk, Sanne
Abstract : In this paper, we consider the Mixed Capacitated General Routing Problem which is a combination of the Capacitated Vehicle Routing Problem and the Capacitated Arc Routing Problem. The problem is also known as the Node, Edge, and Arc Routing Problem. We propose a Branch‐and‐Cut‐and‐Price algorithm for obtaining optimal solutions to the problem and present computational results based on a set of standard benchmark instances. © 2016 Wiley Periodicals, Inc. NETWORKS, Vol. 68(3), 161–184 2016